Evaluation the changes of oral health related quality of life with total maxillary arch distalization during the treatment of class II division 1 malocclusion patients: a randomized controlled trial (Journal of Hama University, 2024)
Aim: The aim of the current study was to evaluate changes in oral health-related quality of life associated with one-Jaw total maxillary arch distalization (1-Jaw TMAD), two-Jaw total maxillary arch distalization (2-Jaw TMAD), and traditional treatment involving upper premolar extractions and en-masse retraction of anterior teeth during orthodontic treatment of Class II division 1 malocclusion.Materials and Methods: Forty-five patients (20 males, 25 females) with Class II Division 1 malocclusion according to the Angle classification were included in the current study. They were randomly assigned to three groups: the first group was treated with TMAD using mini-screw implants between the second premolars and first maxillary molars; the second group was treated with TMAD using inter-maxillary elastics between the maxillary canines and mini-screws between the first and second mandibular molars; and the third group received traditional treatment involving extraction of premolars and mass retraction of anterior teeth with mini-screws between the second premolar and first maxillary molar and en-mass retraction of the anterior teeth.  The Arabic version of oral health impact profile (OHIP-14) which cover 7 domains was used at T0 (Before treatment), T1 (after leveling and alignment), T2 (After 1 month of retraction), T3 (After 6 months of retraction), and T4 (at the end of treatment).Results: Significant deterioration in oral health-related quality of life was observed primarily after one and six months of treatment in the 2-Jaw TMAD group, particularly in the domains of functional limitation, physical pain, physical disability, psychological disability, and the overall OHIP-14 score (medians after one month: 4, 4, 5, 3, 20, respectively; medians after six months: 1, 2, 1, 1, 8, respectively). The greatest negative impact was observed in the control group after one month, particularly in the domains of physical pain and physical disability (medians: 3, 2, respectively). The least significant impact on oral health-related quality of life was observed at the end of treatment compared to baseline scores (medians for total OHIP-14 score: before treatment: 14, 16, 15; after treatment: 3, 4, 2 for 1-Jaw TMAD, 2-Jaw TMAD, and control groups, respectively).Conclusions: All three treatment approaches showed improvement in oral health-related quality of life. The greatest negative impact on oral health-related quality of life was associated with total maxillary arch distalization using two-jaw mechanics, and this impact persisted for six months. total maxillary arch distalization using one-jaw mechanics had the least significant impact on quality of life.
Keywords: total maxillary arch distalization; oral health related quality of life; mini implants; class II division 1 malocclusion